Research Progress in the Molecular Mechanisms, Therapeutic Targets, and Drug Development of Idiopathic Pulmonary Fibrosis - Ma, Hongbo; Wu, Xuyi; Li, Yi; Xia, Yong (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a fatal interstitial lung disease. Recent studies have identified the key role of crosstalk between dysregulated epithelial cells, mesenchymal, immune, and endothelial cells in IPF. In addition, genetic mutations and environmental factors (e.g., smoking) have also been associated with the development of IPF. With the recent development of sequencing technology, epigenetics, as an intermediate link between gene expression and environmental impacts, has also been reported to be implicated in pulmonary fibrosis. Although the etiology of IPF is unknown, many novel therapeutic targets and agents have emerged from clinical trials for IPF treatment in the past years, and the successful launch of pirfenidone and nintedanib has demonstrated the promising future of anti-IPF therapy. Therefore, we aimed to gain an in-depth understanding of the underlying molecular mechanisms and pathogenic factors of IPF, which would be helpful for the diagnosis of IPF, the development of anti-fibrotic drugs, and improving the prognosis of patients with IPF. In this study, we summarized the pathogenic mechanism, therapeutic targets and clinical trials from the perspective of multiple cell types, gene mutations, epigenetic and environmental factors.